2008
DOI: 10.1007/s11738-008-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Genes associated with the release of dormant buds in tree peonies (Paeonia suffruticosa)

Abstract: A subtractive cDNA library was developed to study genes associated with the release of dormant buds in tree peony. To identify genes that are highly expressed in buds released from dormancy, 588 clones were examined by differential screening and then 185 clones were selected to be sequenced. A total of 31 unique genes were obtained, of which only 25 sequences had matches in the NCBI database or Arabidopsis thaliana protein database while 6 sequences with no matches. Many of the different genes were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…PsARP showed a sharp increase prior to bud break and then dropped to low levels as the buds grew [9].…”
Section: Drm1/arp and Dormancymentioning
confidence: 99%
“…PsARP showed a sharp increase prior to bud break and then dropped to low levels as the buds grew [9].…”
Section: Drm1/arp and Dormancymentioning
confidence: 99%
“…In addition, the transcript of PsMYB1 quickly increased after 21 days chilling requirement when transferred to greenhouse for 1 days, but reached peak after enduring 7 days chilling when transferred to greenhouse for 3 days. The buds that received more than 21 days chilling treatment entered the other physiological stage, eco-dormancy (Huang et al 2008a). Our results indicated that the response of PsMYB1 to temperature changes of complete dormancy release might be quicker than its response of dormancy flower buds, which suggested that PsMYB1 might be associated to eco-dormancy and budbreak.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, studies on the tree peony mainly focused on the physiological and horticultural aspects of dormancy, such as nutrient substance, membrane lipid peroxidation and the endogenous hormone changes during the fulfillment of the chilling requirement (Liu et al 2004;Luo et al 2008;Zheng et al 2009). Huang et al (2008a) firstly screened 31 unigenes associated with dormancy release in the tree peony by suppression subtractive hybridization (SSH). But the majority of studies focused mainly on functional genes, with little focus on transcription factors (TF).…”
Section: Introductionmentioning
confidence: 99%
“…High expression levels of ARP were also reported to be associated with dormant bud release in tree peonies (Paeonia suffruticosa; Huang et al 2008). As in tree peonies, the upregulation of ARP might promote sprouting in shortleaf pine after top removal.…”
Section: Hormone-related Genesmentioning
confidence: 97%
“…Recently, several microarray experiments have been carried out to profile genes responsible for dormancy release of buds of perennial trees and perennial grasses (Leida et al 2010;Huang et al 2008;Mazzitelli et al 2007;Pacey-Miller et al 2003). Normally, for a cDNA array, the cDNA clones printed on the slides and the labeled mRNA hybridized to it are from the same species, but researchers have utilized the so-called cross-hybridization.…”
Section: Introductionmentioning
confidence: 99%